IMPLEMENTATION OF PREVENTION AND ERADICATION OF NARCOTICS ABUSE AND ILLEGAL DISTRIBUTION AT THE BNN OF NORTH SUMATERA PROVINCE - Wildan Fahriza; Muhammad Arif Sahlepi; Rahmayanti (PT. Sinergi Legal Publisher, 2024)
This study analyzes the effectiveness of the implementation of Law Number 35 of 2009 concerning Narcotics in North Sumatra Province, focusing on the role of the National Narcotics Agency (BNN) in the Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics (P4GN) program. A juridical-sociological approach is used to evaluate how this law is implemented in a complex social context, as well as how factors such as coordination between institutions, rehabilitation capacity, and community acceptance affect its effectiveness. The findings show that the implementation of this law is often limited to ceremonial activities and is not accompanied by effective follow-up. In addition, limited rehabilitation facilities and lack of coordination between law enforcement agencies are major obstacles. This study recommends the adoption of a more comprehensive approach, including the possibility of legalizing marijuana with strict supervision, which has proven effective in developed countries in reducing the demand for heavy narcotics. This approach should be based on Soerjono Soekanto's law enforcement theory and the principle of maslahah in Islamic law, which emphasizes the importance of community welfare and prevention of harm. Thus, the P4GN policy in North Sumatra can be strengthened to provide maximum benefits and prevent the negative impacts of drug abuse.